2011
DOI: 10.1007/s12011-011-8965-5
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Levels of Zinc, Copper, and Ceruloplasmin in Patients after Undergoing Laparoscopic Adjustable Gastric Banding

Abstract: Laparoscopic adjustable gastric banding (LAGB) causes significant weight loss in morbidly obese adults. However, its consequences on nutritional status still remain unclear. There are a few studies determining the nutritional status after LAGB and none have focused on the serum levels of zinc (Zn), copper (Cu), and ceruloplasmin (CP). We aimed to investigate the effects of LAGB surgery on plasma Zn, Cu, and CP levels. Thirty patients with LAGB with morbid obesity were included. Blood samples were collected pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…This is contrary to the findings of Gletsu-Miller et al, who observed a Cu deficiency in approximately 10% of obese subjects 24 months after participating in bariatric surgery [32], and Kumar et al, who reported that postoperative Cu deficiency is rare [33]. Cu, which is principally stored in the liver, is released to maintain increased requirements of antioxidant enzymes and ceruloplasmin (Cp), a α-2 glycoprotein that incorporates more than 95% of the total Cu in circulation copper [34]; as a result, the level of circulating Cu is dependent on Cp and an ISP [35]. In this study, however, no significant difference was observed between the serum Cp levels in the control and morbid-obesity groups, and a Gelts close association was observed between the Znto-Cu ratio and Lcn2 (r = 0:371, P = 0:002); these results indicate that greater awareness of micronutrients concentrations-including those of multivitamins and TEs used in supplementation-is needed in postoperative plans after an LSG procedure has been performed.…”
Section: Discussionmentioning
confidence: 85%
“…This is contrary to the findings of Gletsu-Miller et al, who observed a Cu deficiency in approximately 10% of obese subjects 24 months after participating in bariatric surgery [32], and Kumar et al, who reported that postoperative Cu deficiency is rare [33]. Cu, which is principally stored in the liver, is released to maintain increased requirements of antioxidant enzymes and ceruloplasmin (Cp), a α-2 glycoprotein that incorporates more than 95% of the total Cu in circulation copper [34]; as a result, the level of circulating Cu is dependent on Cp and an ISP [35]. In this study, however, no significant difference was observed between the serum Cp levels in the control and morbid-obesity groups, and a Gelts close association was observed between the Znto-Cu ratio and Lcn2 (r = 0:371, P = 0:002); these results indicate that greater awareness of micronutrients concentrations-including those of multivitamins and TEs used in supplementation-is needed in postoperative plans after an LSG procedure has been performed.…”
Section: Discussionmentioning
confidence: 85%
“…A positive correlation was found between weight loss and a decrease in serum ceruloplasmin levels. 22 Some studies have reported that high ceruloplasmin concentrations represent an elevated risk for cardiovascular diseases. Considering that conditions such as diabetes, hyperlipidemia, hypertension, and obesity are associated with inflammation and each of them is a factor contributing to cardiovascular risk, it is possible to explain this relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically relevant circumstances predisposing to copper deficiency can include prolonged unsupplemented total parental nutrition (TPN) or enteral nutrition, infants fed with unmodified cow milk based diets, prematurity, gastric bypass and laparoscopic adjustable gastric banding surgery, burns, malabsorption syndromes, and large doses of over the counter vitamins containing zinc and iron [3]. Loss of ceruloplasmin bound copper can also occur in patients undergoing continuous ambulatory peritoneal dialysis for renal failure [4].…”
Section: Introductionmentioning
confidence: 99%